P175 MASTERPLANS: prediction of response to rituximab in SLE using a validated two-score system for interferon. (20th April 2020) - Alase, Ade; Wigston, Zoe; Burska, Agata; Yusof, Yuzaiful Md; Reynolds, John; Consortium, The MASTERPLANS; Wittmann, Miriam; Bruce, Ian; Vital, Edward M
Abstract: Background: Rituximab is used for resistant SLE, but clinical response varies. We previously validated two interferon-stimulated-gene expression scores (IFN-Score-A and IFN-Score-B) that improved prediction of clinical outcomes in SLE. IFN-Score-A included most reported ISGs and predicted flares and glucocorticoid requirements. IFN-Score-B included ISGs that respond to multiple IFN subtypes and predicted development of SLE in At-Risk individuals. Diagnosis of SLE was associated with both scores, while only IFN-Score-B was elevated in RA. The British Society for Rheumatology Biologics Registry (BILAG-BR) collects samples for RTX-treated patients in the UK. MASTERPLANS ISA consortium to identify predictors of drug response. Methods: Patients were recruited if they were starting a first cycle of RTX for active SLE (BILAG A or 2xBILAG B) despite previous cyclophosphamide or mycophenolate mofetil. Disease activity was measured using BILAG-2004. Clinical response was defined as improvement by > =1 grade in active BILAG-2004 systems with no worsening in other systems. Whole blood was collected into TEMPUS tubes and RNA extracted. IFN-Scores were measured using a custom Taqman array as previously described [El Sherbiny et al., 2018]. Multivariate logistic regression was used to test IFN-Scores and baseline clinical covariates as predictors of BILAG response at 6 months. Results: Samples were available from 147 patients, of whom 84 had complete baseline and 6-month clinical data available and were included in this analysis. 40/84 (47.6%) patients had BILAG response at 6 months. In univariate and multivariate analysis, high IFN-Score-B expression was significantly associated with clinical response (see Table 1). Conclusion: This preliminary analysis suggests that assessment of IFN activity has a role in predicting response to RTX. A novel IFN score (Score B) was more predictive than classic ISGs (Score A). These results add to a body of work showing that IFN-Score-B predicts clinically significant outcomes independently of overall IFN activity. Future work will analyse this biomarker in a larger cohort of patients and integrate with other putative clinical and biological predictors of response. Disclosures: A. Alase None. Z. Wigston None. A. Burska None. M. Md Yusof None. J. Reynolds None. M. Wittmann None. I. Bruce None. E.M. Vital None.